MANFAAT SLIMS 9 BULIAN UNTUK KATALOG DI PERPUSTAKAAN SMPN 3 JAMPANGTENGAH - Ade Setiawan; Evi Nursanti Rukmana; Asep Saeful Rohman (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
Knowledge is an important thing, especially in improving human resources, one of which is receiving education in schools. supporting knowledge in schools, namely school library facilities. The purpose of this study was to find out how the benefits of SLiMS as a digital catalog in processing library materials in the school library. The research method used was descriptive qualitative method with observation data collection techniques, literature studies and interviews with informants consisting of one librarian at SMPN 3 Jampangtengah. The results showed that the processing of library materials at SMPN 3 Jampangtengah is still conventional, therefore it is necessary to use SLiMS in processing library materials, especially in cataloging in order to make it easier to retrieve information and also store library material data in the SLiMS application. especially cataloging is very important in information retrieval in libraries, using SLiMS will make it easier to catalog and retrieve information efficiently.